A Case of Noncompaction at All Segments of Both Right and Left Ventricles - Ali Pourmoghaddas; Reihaneh Zavar; Mohaddeseh Behjati (Case Reports in Cardiology)
Background. Noncompaction/hypertrabeculation left ventricle (NCM/HVM) is most commonly reported in one or more segments of left ventricle and sometimes both ventricles. In this case, we present noncompaction of all segments of right and left ventricle, in a young man with mental retardation. Case Presentation. A 19-year-old male was referred to us with sudden dyspnea at rest and chest discomfort. He was a known case of mental retardation. He was born full term with birth weight = 1250 grams. On physical examination. A systolic murmur (II/VI) at left sternal border was heard. ECG showed increased voltage in precordial lead and deep ST segment depression. Chest X-ray (CXR) was within normal limits. Transthoracic echocardiography showed situs solitus, D loop, normal connection of great vessels, noncompaction LV at all segments (noncompaction/compaction = 2.5/0.5) with moderate systolic dysfunction (LVEF = 40%), diastolic dysfunction grade II, normal RV size with mild systolic dysfunction and hypertrabeculation, mild tricuspid regurgitation (TR), and normal pulmonary artery systolic pressure. After injection of agitated saline some bubbles were passed from right to left through patent foramen oval (PFO). Conclusions. Extensive sinusoid formation and trabeculation of RV and nearby all LV segments and its association with mental retardation suggest presence of strong genetic background.